The psychology of relationships - Willerton, Julia (New York, NY : Palgrave MacMillan, 2010)
'This introduction focuses on the key aspects of human relationships including their development, maintenance and breakdown. Ideal for students who want a more rounded and detailed text on this area, the author discusses the role of evolution, individual differences and the effects of relationships on mental and physical health'--
Studying relationships : perspectives and methods -- An evolutionary perspective on human relationships -- The effects of early experience on relationships -- Getting relationships started -- Breakdown of relationships -- Cultural variations in relationships -- Effects of relationships.
Includes bibliographical references (p. 169-190) and index.
Keywords: Interpersonal relations -- Psychological aspects